Person-centred care: what is it and how do we get there? - Coulter, A; Oldham, J (Royal College of Physicians, 2016)
This edition of Future Hospital Journalhas a focus on personcentred care and explores the dimensions to partnership working at three different levels – consultation, service and system levels. In this introduction the authors explain what they consider to be the essential components of person-centred care and what needs to be done to embed it at all levels of healthcare delivery. The changing attitudes of patients and the desire of most of them to receive personalised care based on their individual needs, preferences and lifestyles are explored. It is argued that a culture change is needed to make person-centred care the norm and that patients can help deliver this through a more meaningful involvement in medical research, training and education, service reconfiguration and commissioning.